PROFIL USAHA RUMAH KOPI MONOCAFE DI KELURAHAN WENANG SELATAN KOTA MANADO - Renovaldo Imanuel Apituley; Benny Adrian Berthy Sagay; Jean Fanny Junita Timban (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the business profile of Manado Monocafe Coffee House and to find out how much profit from the Monocafe Coffee House business that sells coffee and food drinks. This research was conducted at Monocafe Coffee House in Wenang Selatan Village, Manado City. Data retrieval is done by direct interview with the coffee house owner (one respondent). Data collected is the characteristics of business actors, financial aspects, management aspects, technical and production aspects, marketing aspects, and profits. Secondary data was obtained from the Monocafe Coffee House business profile, local book store, internet through google searching to obtain journal articles and thesisrelated to the research topic about the business profile of Monocafe Coffee House. Data analysis using descriptive analysis and profit analysis. The results showed that the Monocafe Coffee House business was a small business. Started operating since 2016 by using its own capital. The amount of coffee rawmaterial used in one month (in August 2018) is 6 Kg producing 1,156 drinks and 662 food items. The advantage obtained with the R / C> 1 ratio is 1.40. This means that in August 2018 the Monocafe Coffee House business has benefited so that this business is worthy of continuing.-*eperm*